17th International IEEE Conference on Intelligent Transportation Systems (ITSC) 2014
DOI: 10.1109/itsc.2014.6957839
|View full text |Cite
|
Sign up to set email alerts
|

Capacity drops at merges: New analytical investigations

Abstract: This paper focuses on the derivation of analytical formulae to estimate the effective capacity at freeway merges. It extends previous works by proposing a generic framework able to account for (i) heterogeneous vehicle characteristics and (ii) refined description of the physical interactions between upstream waves and downstream voids created by inserting vehicles within the merge area. The provided analytical formulae permit to directly compute the capacity values when the merge is self-active, i.e. when both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Chen et al (2014) 2010, Leclercq et al 2011Leclercq et al , 2015 Inter-driver/vehicle spread indicates the spread of drivers and vehicles. Papageorgiou et al (2008) state that the capacity drop is due to the acceleration difference between two successive vehicles.…”
Section: Overview Of Assumptions On Mechanisms Of the Capacity Dropmentioning
confidence: 99%
“…Chen et al (2014) 2010, Leclercq et al 2011Leclercq et al , 2015 Inter-driver/vehicle spread indicates the spread of drivers and vehicles. Papageorgiou et al (2008) state that the capacity drop is due to the acceleration difference between two successive vehicles.…”
Section: Overview Of Assumptions On Mechanisms Of the Capacity Dropmentioning
confidence: 99%
“…Each merge has only one targeted lane for the insertions. The analytical expressions for the effective capacity, C 1 and C 2 for the related inserting flows q 0 and q 12 , respectively, can then be derived directly from the analytical formulas provided elsewhere (24,29). It is beyond the scope of this paper to explain how these formulas were derived.…”
Section: Analytical Expression Of Effective Capacity For a Given Inserting Flowmentioning
confidence: 99%
“…The authors recall only the main hypothesis and provide the formulation when vehicle characteristics are homogeneous. The readers are referred in particular to the work of Leclercq et al for details and extension to the heterogeneous case (29).…”
Section: Analytical Expression Of Effective Capacity For a Given Inserting Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that merging from the acceleration lane has a significant impact on traffic operations at freeway on-ramp bottlenecks [1,2] and can also trigger traffic breakdown [3][4][5]. Merging behavior is a complex task, because, typically, the driver has to focus on three or more vehicles in their current and target lanes in a limited timeframe [5].…”
Section: Introductionmentioning
confidence: 99%